Comprehensive Review of Human Papillomavirus (HPV) Vaccination Recommendations for Boys and Young Men (Journal of the Medical College for Women & Hospital, 2026)
Human papillomavirus (HPV) , a most common infection transmitted sexually, has significant implications for both males and females. It includes genital warts and a range of anogenital and oropharyngeal cancers. While early vaccination efforts primarily targeted girls to reduce cervical cancer rates, increasing recognition of HPV-related diseases in boys and young men has prompted major changes in vaccination guidelines. This review provides a comprehensive overview of the importance of and current recommendations regarding HPV vaccination in males. Boys and young men are at risk for disfiguring and psychologically distressing genital warts, as well as malignant outcomes including anal and penile cancers. Furthermore, males contribute a significant part in the transmission of HPV to sexual partners, underscoring the population-level benefits of widespread immunization. Clinical studies demonstrate high efficacy of HPV vaccines when administered before exposure, and current recommendations from agencies such as the CDC, ACIP, and AAP endorse routine vaccination for boys starting at ages 11–12, with catch-up vaccination up to age 26, and special attention  to individuals with HIV and men having sexual encounters with partners from their own gender. Vaccine schedules have recently been updated, with evidence supporting a one-dose regimen for individuals under 25 years of age. Available vaccines protect against the major oncogenic types (16 and 18) and those causing most genital warts (6 and 11), with broader protection offered by the nonavalent vaccine. The adoption of routine HPV vaccination in boys and young men promises to reduce disease burden and transmission, and ongoing research and educational initiatives remain key to optimizing public health impact.J Med Coll Women Hosp.2026; 22(1): 178-187